2005
DOI: 10.1124/dmd.105.007757
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the P-Glycoprotein-Mediated Intestinal Secretion of Ivermectin: In Vitro and in Vivo Assessments

Abstract: ABSTRACT:The everted gut sac method was used to assess the role of the P-glycoprotein (P-gp) on the intestinal secretion of ivermectin (IVM), an antiparasitic widely used in human and veterinary medicine. The work included the evaluation of two different P-gp modulators [itraconazole (ITZ) and valspodar (PSC833)] used at equimolar doses in the rat. Furthermore, the influence of both P-gp modulator agents on the disposition kinetics of IVM in plasma, liver, and gastrointestinal tissues was characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 27 publications
1
54
0
Order By: Relevance
“…Ivermectin is eliminated mostly unchanged in bile and feces (González Canga et al, 2009) and so, as a P-gp substrate, it is a candidate for secretion by the liver or intestine. Thus, the possibility that systemic ivermectin concentrations increase as a result of spinosad inhibition of secretion should be considered, especially because ivermectin is known to undergo P-gp-mediated exsorption in rodents (Sparreboom et al, 1997;Laffont et al, 2002;Ballent et al, 2006). As an alternative, the increase in the dog ivermectin C max and lack of change in the terminal half-life could suggest that spinosad increased the oral fraction of ivermectin absorbed.…”
Section: Discussionmentioning
confidence: 99%
“…Ivermectin is eliminated mostly unchanged in bile and feces (González Canga et al, 2009) and so, as a P-gp substrate, it is a candidate for secretion by the liver or intestine. Thus, the possibility that systemic ivermectin concentrations increase as a result of spinosad inhibition of secretion should be considered, especially because ivermectin is known to undergo P-gp-mediated exsorption in rodents (Sparreboom et al, 1997;Laffont et al, 2002;Ballent et al, 2006). As an alternative, the increase in the dog ivermectin C max and lack of change in the terminal half-life could suggest that spinosad increased the oral fraction of ivermectin absorbed.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, for moxidectin, the contribution of P-gp in these processes was weak as shown by the lack of change of moxidectin plasma kinetics in mdr1ab(Ϫ/Ϫ) mice. P-gp is known to be partly responsible for MLs elimination by the fecal route via intestinal excretions (Laffont et al, 2002;Ballent et al, 2006). Thus, we have compared the capacity of the intestine to eliminate these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…MLs are poorly metabolized (Chiu et al, 1987;Alvinerie et al, 2001) and are good substrates and potent inhibitors of P-gp (Didier and Loor, 1996;Pouliot et al, 1997;Lespine et al, 2007). P-gp protects the brain from MLs by limiting their penetration across the blood-brain barrier and thus their subsequent neurotoxicity (Schinkel et al, 1994;Lankas et al, 1997;Roulet et al, 2003), and it contributes to the elimination of ivermectin via intestinal excretion (Laffont et al, 2002;Ballent et al, 2006). Moreover, P-gp-mediated drug efflux has been suggested as a protection mechanism in nematodes, and several P-gp homologs are overex-pressed in ivermectin resistance (Prichard and Roulet, 2007).…”
mentioning
confidence: 99%
“…This model has also been reported to be applicable to both rat and mouse, and to study the phase I and phase II metabolism as well as transport. Inhibition studies of enzymes and transporters, such as CYP3A4 and MDR1, have also been reported (Hashimoto et al, 1998;Ballent et al, 2006). However, the major disadvantage of this model is that the lack of blood and nerve supply can lead to a rapid loss of tissue viability.…”
Section: Animal Tissue-based In Vitro Methodmentioning
confidence: 99%